2016
DOI: 10.1002/tesq.296
|View full text |Cite
|
Sign up to set email alerts
|

The Linguistic Development of Students of English as a Second Language in Two Written Genres

Abstract: This study examined narrative and argumentative essays written over the course of a 4‐month semester by 37 students of English as a second language (ESL). The essays were analyzed for development over time and for genre differences. The goal of the study was to conceptually replicate previous studies on genre differences (e.g., Lu, 2011) and on short‐term linguistic development in the areas of syntactic complexity, accuracy, lexical complexity, and fluency (e.g., Connor‐Linton & Polio, ). In addition, the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
126
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(145 citation statements)
references
References 47 publications
(113 reference statements)
15
126
3
1
Order By: Relevance
“…Similar differences can be observed when syntactic complexity is assessed in different genres, like fiction, drama, newspapers, narratives, argumentative essays, monologues or interactive speech. Yoon and Polio, (), for instance, found higher scores for syntactic complexity in argumentative essays compared to narratives. Until now, however, there have been only a few studies which have investigated the effect of genre on L2 syntactic complexity (but see Biber & Gray, ; Biber et al, 2011, 2016; Polio & Park, ).…”
Section: Variation In Syntactic Complexitymentioning
confidence: 99%
“…Similar differences can be observed when syntactic complexity is assessed in different genres, like fiction, drama, newspapers, narratives, argumentative essays, monologues or interactive speech. Yoon and Polio, (), for instance, found higher scores for syntactic complexity in argumentative essays compared to narratives. Until now, however, there have been only a few studies which have investigated the effect of genre on L2 syntactic complexity (but see Biber & Gray, ; Biber et al, 2011, 2016; Polio & Park, ).…”
Section: Variation In Syntactic Complexitymentioning
confidence: 99%
“…Szmrecsanyi (), for instance, found very high correlations ( r = .976 – .989) between length measures and syntactic node counts in both written and oral English data. Previous research practices, however, have been criticized for focusing almost exclusively on syntactic length at the supraclausal level (e.g., Terminal (T)‐units in writing research [Hunt, ], Analysis of Speech (AS)‐units in spoken language research [Foster, Tonkyn, & Wigglesworth, ]), while complexity may manifest itself differently at other syntactic levels, notably the phrasal and clausal level, reflecting proficiency, modality, or genre differences (Biber & Gray, ; Biber et al., ; Byrnes et al., ; Kuiken & Vedder, , ; Norris & Ortega, ; Pallotti, ; Yoon & Polio, ). With regard to the phrasal level, Norris and Ortega () have argued that phrasal elaboration constitutes an advanced area of syntactic development, particularly in formal and academic writing.…”
Section: Defining and Measuring Syntactic Complexitymentioning
confidence: 99%
“…For instance, the degree of interactionality has been found to influence complexity in the sense that monologic tasks facilitate the use of higher syntactic elaboration more than dialogic tasks (Michel, Kuiken, & Vedder, 2007). Another study on L2 writing in different genres (Yoon & Polio, 2016) also found significant differences in terms of syntactic elaboration at the level of the phrase, clause, sentence, and T-unit between argumentative and narrative writing, but found no differences for syntactic subordination. Moreover, Ferrari (2012) remarks that effective communication in some tasks can be associated with simpler language, while Lambert and Kormos (2014) similarly emphasize that successful communication may be a matter of "practiced mastery in efficient and effective message formation" (p. 612), rather than the use of increasingly complex language.…”
Section: A Cross-linguistic Perspective On the Development Of Syntactmentioning
confidence: 99%
See 1 more Smart Citation
“…Syntactic complexity is generally construed as the variety and degree of sophistication of the syntactic structures that are present in a text (Housen & Kuiken, 2009;Lu, 2011;Ortega, 2003;Pallotti, 2009). As part of the larger construct of linguistic complexity (Bulté & Housen, 2014), it has been considered to be a critical component in assessing the readability or comprehensibility of original and adapted reading texts for both first and second language (L2) readers (Berendes et al, 2018;Crossley et al, 2007;Frantz et al, 2015;Gamson et al, 2013;Graesser et al, 2011;Stevens et al, 2015), as well as a useful index of language proficiency (e.g., Bulté & Housen, 2014;Lu, 2011;Norris & Ortega, 2009), language development (e.g., Crossley & McNamara, 2014;Lu, 2009;Yoon & Polio, 2017), and the quality of language production (e.g., Biber, Gray, & Staples, 2016;Kyle & Crossley, 2018;Lu, 2017;Yang, Lu, & Weigle, 2015).…”
Section: Measuring Syntactic Complexitymentioning
confidence: 99%